The Instagram Comics as Learning Media Alternative to Improve Learning Materials on Light Refraction during the COVID-19 Pandemic - Salsabilla, Sasqia Shafa; Pratama, Bagus; Pangestu, Dimas Aji; Setiaji, Bayu (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2022)
In the era of the Covid-19 pandemic, teaching and learning processes were not allowed to be carried out directly or face to face but could be carried out indirectly or remotely. This requires teachers to be able to use existing technology along with the times. One trend that is currently emerging is the use of social media as a learning medium. This study develops one of the learning media using comics with the help of social media, Instagram. This study aims to determine the level of feasibility of Instagram comic-based learning media as an alternative to learning during the Covid-19 pandemic to increase students' learning motivation on light refraction material. The research method used is the research and development method with the 4D model method. The findings of this study are that Instagram comics can be used as an alternative learning media during the covid-19 pandemic to increase students' learning motivation on light refraction material. Based on the stages that have been carried out, the results of the feasibility test of the Instagram comic learning media product are declared very feasibly.